Robust training algorithm of neural network for pattern recognition and control - Song, Qing. (2008)
This report focuses on the neural networks and their application in the fault monitoring. A neural network based fault monitoring system is presented for a classs of discrete-time nonlinear systems. The neural network plays an important role of function approximator in the fault monitoring system.